The Violation of Human Rights in Latin America Derived from the Covid-19 Pandemic Administration - Ricardo Furfaro (European Scientific Journal, ESJ, 2022)
There is no doubt at this stage of the solid evolving global relevance of universal human rights in a complex global scenario like everyone faces today. The COVID-19 pandemic and lockdowns have produced, and are still causing, an overwhelmingly negative impact on the standard citizens’ lives. As drastic as it is, such affirmation is sustained in the serious deterioration in a considerable number of democracies around the world, but especially reflected in Latin America, a region of six hundred (600) million inhabitants (Werthein & Abrantes, 2021). This research aims to assess the scope of the violation of individuals’ basic human rights caused by the COVID-19 pandemic administration in Latin American countries. Unreasonably extended lockdowns and other misleading and inappropriate measures implemented by different Latin American administrations have had unsurmountable and dramatic consequences for the region's inhabitants. Many Latin American governments have inadvertently put in place two (2) excluding options for their populations affected by the COVID-19 pandemic. It had to be either healthcare and fight against COVID-19, on the one side, or economic sustainability, on the other, but not the two (2) simultaneously.  Losses of thousands of lives, economic devastation, thousands of business shutdowns, millions of job losses, and educational catastrophes have all affected essential freedoms and individuals’ basic universal human rights recognized by modern constitutions, including those in Latin America.  As discussed, these are the resulting consequences of governments’ failure to build up necessary resources, be readily prepared to face catastrophes of this sort, and act with integrity and transparency in managing public funds. Both quantitative (i.e.numbers and statistics) and qualitative (i.e., secondary data) methodologies have been used to arrive at very relevant conclusions. Sustainable results of this research reflect how mismanagement of the pandemic, including corruption practices by certain Latin American governments, has led to catastrophic consequences in healthcare and the economic field.